Future irrigation water requirements in the Ijuí River basin, RS - Kayoma K. da Silva; Tirzah M. Siqueira; Katiucia N. Adam; Andréa S. Castro; Luciara B. Corrêa; Diuliana Leandro (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Changes in temperature and precipitation intensity and frequency have influenced the water demand for irrigation. Regions that have agriculture-based economies, as in the Ijuí River basin, are often affected by periods of drought or excessive rainfall, which is harmful for agricultural productivity. This study aimed to evaluate future irrigation water demands of four crops in this basin (bean, corn, wheat and soybean), comparing them with a baseline period. Meteorological data forecasts were obtained from the regional climate model ETA 40 CTRL for the climatic scenario A1B, for the baseline (1961-1990) and future (2011-2100) periods. The one-dimensional SWAP model was used to estimate the water demand for irrigation. The results showed that, in the future, irrigation water requirements will be smaller for all crops. In the short term (2011-2040), water demands were similar to those for the baseline period, but from the middle of the century onwards (2041-2100), greater reductions were observed.